Search for dark photons in decays of Higgs bosons produced in association with Z bosons in proton-proton collisions at √s = 13 TeV; Journal of High Energy Physics; Vol. 2019, iss. 10 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Asilar E. Ece; Bergauer T. Thomas; Babaev A. A. Anton Anatoljevich; Yuzhakov A. D. Aleksandr Dmitrievich; Okhotnikov V. V. Vitaly Vladimirovich (2019, 2019)
Title screen